485 Effects of Gestation and Lactation on Water Consumption in Lines of Mice Divergently Selected for Water Consumption. (10th April 2018) - Magee, D; Goldkamp, A; Haag, M T; Leffeler, E; Sharp, K; Lamberson, W R
Abstract: Pressure to reduce resource usage are occurring in all segments of our society. Animal agriculture is no exception; with increasing population food producers are expected to produce more food while maintaining a small environmental footprint. One method to reduce water usage is to identify genes regulating water consumption in inbred mouse strains, and translate that information to livestock. Lines divergent for water consumption, C57 Brown/cdj (BR) and C57 Black/10J (BL), are being used to understand how certain environmental and physiological changes affect consumption. The objective of this project is to identify the effects of gestation and lactation on water consumption. To evaluate these effects, we collected daily water consumption data and weekly weight data on female mice of both strains during gestation and two weeks post-partum and on non-gestating and non-lactating controls. Consumption data were corrected for metabolic body weight (wt 0.67 ) prior to analysis, so water consumption is expressed in milliliters consumed per gram of metabolic body weight per day. Brown animals, regardless of pregnancy status, consumed more water (P<0.05) than Black animals (n = 12 BR and n = 10 BL) at all time points (Week 1 Gestation: 0.43 ± 0.04 vs 1.23 ± 0.20, Week 2 Gestation: 0.47 ± 0.04 vs 1.19 ± 0.17, Week 3 Gestation: 0.51 ± 0.07 vs 1.29 ± 0.39, Week 1 Post-Partum: 0.92 ± 0.42 vs 1.23 ± 0.75, Week 2 Post-Partum: 1.27 ± 0.40 vs 2.54 ± 0.32). No difference was observed due to pregnancy status within strain during gestation; however, consumption increased (P<0.05) during lactation in both the Black and Brown strains (Week 1 Post-Partum Blacks: 0.45 ± 0.04 vs 1.14 ± 0.34, Week 2 Post-Partum Blacks: 0.43 ± 0.03 vs 1.27 ± 0.41, Week 1 Post-Partum Browns: 1.15 ± 0.11 vs 2.11 ± 0.40, Week 2 Post-Partum Browns: 1.21 ± 0.20 vs 2.54 ± 0.32). This indicates that both strains respond in a comparable manner to the increased energy demands of lactation regardless of baseline consumption amounts.